1981
DOI: 10.3171/jns.1981.54.2.0252
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous carotid-cavernous fistula during pregnancy or in the postpartum stage

Abstract: The authors report two cases of spontaneous carotid-cavernous fistula that occurred during pregnancy. One patient was a 21-year-old woman whose symptoms improved and in whom disappearance of the carotid-cavernous fistula was confirmed by cerebral angiography after she aborted in the 12th week of pregnancy. The other patient was a 25-year-old woman in whom a carotid-cavernous fistula occurred at about the 28th week of pregnancy. The symptoms became aggravated 3 weeks after a normal delivery. Carotid-cavernous f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 7 publications
1
18
0
1
Order By: Relevance
“…3 However, spontaneous improvement of CCFs during or just after pregnancy appears to be rare. 9 Toya et al 10 reported such an occurrence in a patient with a dural CCF, which ensued 21 days after an abortion at 12 weeks of gestation. Hirata et al 9 described a case of marked regression of a CCF 2 to 3 days after delivery, and speculated that spontaneous improvement in CCF after pregnancy was due to cavernous sinus thrombosis related to changes in blood coagulation that occur during pregnancy and delivery.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, spontaneous improvement of CCFs during or just after pregnancy appears to be rare. 9 Toya et al 10 reported such an occurrence in a patient with a dural CCF, which ensued 21 days after an abortion at 12 weeks of gestation. Hirata et al 9 described a case of marked regression of a CCF 2 to 3 days after delivery, and speculated that spontaneous improvement in CCF after pregnancy was due to cavernous sinus thrombosis related to changes in blood coagulation that occur during pregnancy and delivery.…”
Section: Discussionmentioning
confidence: 99%
“…4,51,66,87 Factors thought to contribute to the breaks in these vessels include arterial hypertension, atherosclerotic vascular disease, pregnancy, minor trauma, straining, diabetic vascular disease, and collagen vascular disease. 44,51,65,72,77 …”
Section: Spontaneous Ccfsmentioning
confidence: 99%
“…Some isolated case series have hinted that some of these patients may undergo an angiographic pattern conversion on long-term follow-up. 3,[12][13][14][15][16][17][18][19][20][21][22] However, many of these patients had been treated palliatively and there is still controversy on whether or how often these lesions may actually show an evolutive pattern conversion without any treatment alterations. 23,24 The purpose of this study is to define the incidence, clinical, and angioarchitectural characteristics of patients with cranial DAVS showing natural temporal pattern conversions on diagnostic subtraction angiography (DSA) based on the long-term follow-up data from a large single-center database.…”
mentioning
confidence: 99%